2023
DOI: 10.3390/electronics12122581
|View full text |Cite
|
Sign up to set email alerts
|

Diplin: A Disease Risk Prediction Model Based on EfficientNetV2 and Transfer Learning Applied to Nursing Homes

Abstract: In the context of population aging, to reduce the run on public medical resources, nursing homes need to predict the health risks of the elderly periodically. However, there is no professional medical testing equipment in nursing homes. In the current disease risk prediction research, many datasets are collected by professional medical equipment. In addition, the currently researched models cannot be run directly on mobile terminals. In order to predict the health risks of the elderly without relying on profes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…FP means that the wrong prediction is a positive example. For example, FN indicates that the wrong prediction is a counterexample [2,3].…”
Section: Evaluation Metricsmentioning
confidence: 99%
See 1 more Smart Citation
“…FP means that the wrong prediction is a positive example. For example, FN indicates that the wrong prediction is a counterexample [2,3].…”
Section: Evaluation Metricsmentioning
confidence: 99%
“…Current research on disease risk prediction mainly uses physiological indicators and risk factors to predict disease risk [1], images to predict disease risk [2], and audio to predict disease risk [3]. These studies have achieved good results.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the realm of education emerges as a particularly promising domain in this era of innovation. This research stands at the forefront of these developments, actively contributing to the creation of a state-of-the-art teacher robot that seamlessly integrates [1], [2]. A primary and innovative focus of this endeavor lies in the infusion of emotional intelligence (EI) into robot teachers, achieved through the sophisticated analysis of facial expressions using advanced artificial intelligence techniques [3], [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies [5][6][7] examining the susceptibility of downstream models to attacks have confirmed that transfer learning can protect these downstream models from being easily attacked, thereby enhancing their robustness. Due to its practicality, transfer learning has attracted extensive attention in the field of computer vision [8][9][10][11][12], and has been applied in many task scenarios such as transportation, medical treatment [13], social media [14] and art [15][16][17][18]. Various works [19] have been proposed to explore the problem of what and how to transfer from the pre-trained models.…”
Section: Introductionmentioning
confidence: 99%